PRINSIP-PRINSIP KAIZEN JEPANG DALAM PERSPEKTIF AL-QURâAN DAN SUMBANGANNYA BAGI PSIKOLOGI PENDIDIKAN ISLAM - Rahmatullah, Azam Syukur (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2014)
Abstract: The paper discuss and study about Kaizen principle, that is Japanese culture principle and its quality have to attest and aims to point of successfully both individual and group also. This Kaizen principle substances and values that contained in it apparently have discussed long time ago by founding further of Islam, and have taught in al-Qurâan. Unfortunately the people who studied it and become expert precisely are Japanese people that isnât moslem/Islam. So, in this short paper will explain the strong relevance/great relevance between Kaizen principle and al-Qurâan and also the implication for the psychology of Islamic Education.